Low density porous carrier based conceptual drug delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Pawar, Atmaram P. (Microporous and Mesoporous Materials, 2007)
Chronotherapy, a new approach for treating pathological conditions, is based on circadian rhythm. Present work conceptualizes a specific technology, based on combining floating and pulsatile principles to develop drug delivery system, intended for chronotherapy in arthritis. This approach was achieved by using low density microporous polypropylene, Accurel MP 1000 (R), as a multiparticulate carrier along with drug of choice ibuprofen. Carrier amount and solvent volume was kept invariant in designing this simple system by adsorbing drug via melting or solvent evaporation using different carrier: drug ratios. In solvent evaporation, methanol (M) and dichloromethane (DCM) were used. Drug loaded multiparticulate system was subjected to various characterization and evaluation parameters showing influence of adsorption process. Drug release study was performed in acidic environment using pH 1.2 HCl IP medium for 6 h to mimic gastric condition for evaluating gastroretention followed by basic environment using appropriate medium as phosphate buffer pH 7.2 IP for 3 h resembling transit. The release pattern showed influence of drug adsorption methods characterized by ever changing pore geometry with total release ranges in acidic medium as 10.7-27.6% and final release as 55.6-88.6%. Present drug delivery system devoid of any additives/excipients influencing drug release show distinct behaviour from other approaches/technologies in chronotherapy by (a) observing desired low drug release (11%) in acidic medium (b) overcoming the limitations of process variables caused by multiple formulation steps (c) reducing time consumption due to single step process (d) can be extended to controlled release also. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: chronotherapy; floating pulsatile drug delivery; low density porous carrier; melt adsorption; solvent polarity

Low density porous carrier - drug adsorption and release study by response surface methodology using different solvents - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Pawar, Atmaram P. (International Journal of Pharmaceutics, 2007)
Low density porous carriers are widely used in the pharmaceutical applications. Response surface methodology, using 3 2 factorial design was used to study drug adsorption on and its release patterns from microporous polypropylene (Accurel MP 1000((R))) in the absence of additives. Ibuprofen, as model drug, was adsorbed on the polymer by solvent evaporation using two organic solvents methanol (M) and dichloromethane (DCM). The amount of carrier (100 mg) and its particle size range (250-350 mu m) were kept invariant while solvent volume (X-1) and drug amount (X-2) were taken as variables. Drug adsorption pattern depended on the type and amount of solvent used. DSC, XRD, FTIR and TGA, predict crystalline nature and physical form of adsorption. SEM showed the penetration and adsorption of the drug in and on the microporous polymer. Accurel NIP 1000((R)) had a pore volume of 1.992 g/cm(3) and surface area of 55.9855 m(2)/g as detected by mercury porosimetery. On drug adsorption, pore volume ranged from 0.413 to 1.198 g/cm(3) for methanol and 0.280-0.759 g/cm(3) for DCM. Similarly surface area was in the range 38.445-25.497 m(2)/g for methanol and 18.710-32.528 m(2)/g for DCM. The drug release was investigated in phosphate buffer pH 7.2. All batches showed excellent in vitro floating property. Drug release was partial with recovery to complete dependent on type and volume of solvent. R 2 values relating to bulk density, pore volume, surface area and drug release at 60, 120 and 180 min were estimated. Effect of solvent properties shows a positive influence on drug adsorption and release. Release profiles of some batches could be considered as gastroretentive drug delivery system. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 3(2) factorial design; carrier; microporous polymer; Response surface methodology; solvent evaporation